A novel polyhedral oligomeric silsesquioxane-modified layered double hydroxide: preparation, characterization and properties - Zhang, Xianwei; Ma, Zhongzhu; Fan, Hong; Bittencourt, Carla; Wan, Jintao; Dubois, Philippe (Beilstein Journal of Nanotechnology, 2018)
A novel layered double hydroxide modified by octa-substituted carboxy-terminated polyhedral oligomeric silsesquioxane was prepared via a one-step method and characterized by Fourier-transform infrared spectroscopy, X-ray photoelectron spectroscopy, X-ray diffraction, transmission electron microscopy, scanning electron microscopy, elemental analysis, thermogravimetric analysis, and microscale combustion calorimetry (MCC). Results showed that the silsesquioxane modified-LDH (OLDH) revealed an increase in the interlayer distance, nanoscale plate-like morphology of primary particles, and improved thermal stability. A synergistic effect between the siloxane moiety and Mg–Al hydroxide was found during thermal degradation, and confirmed by the study of degradation kinetics together with the analysis of the surface morphologies and elemental components of char residues. Moreover, in contrast to conventional organic modified LDH (e.g., dodecylbenzenesulfonate-LDH), the MCC results showed a significant decrease in the heat release rate and total heat release, indicating the low flammability of OLDH.
Keywords: flammability; layered double hydroxide; polyhedral oligomeric silsesquioxane; thermal stability